2012
DOI: 10.1111/j.1442-2050.2012.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline nutritional status is prognostic factor after definitive radiochemotherapy for esophageal cancer

Abstract: Identify prognostic factors for survival and patterns of treatment failure after definitive radiochemotherapy for esophageal cancer. Between 2003 and 2006, 143 patients with squamous cell carcinoma and adenocarcinoma of the esophagus were retrospectively reviewed. Median age was 65 years (42-81). Median radiation dose was 62.5 Gy (38-72) with 1.8-2 Gy fraction. Median follow-up was 20.8 months (2.8-92.4). Three and 5-year local recurrence-free survival rates were 58.3% and 50.9%. In univariate analysis, traver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 32 publications
(75 reference statements)
7
46
1
2
Order By: Relevance
“…NRI is another tool used for the assessment of malnutrition based on serum albumin concentration and weight loss. Ιncreased nutritional risk, derived from NRI, is associated with reduced survival in esophageal cancer patients treated with definitive chemoradiotherapy [10,33], but is not associated with postoperative infectious complications in patients treated with esophagectomy [27]. The Geriatric Nutritional Risk Index (GNRI) is a new index recently introduced for the assessment of nutritional status of elderly patients.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 99%
“…NRI is another tool used for the assessment of malnutrition based on serum albumin concentration and weight loss. Ιncreased nutritional risk, derived from NRI, is associated with reduced survival in esophageal cancer patients treated with definitive chemoradiotherapy [10,33], but is not associated with postoperative infectious complications in patients treated with esophagectomy [27]. The Geriatric Nutritional Risk Index (GNRI) is a new index recently introduced for the assessment of nutritional status of elderly patients.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 99%
“…The median overall survival was reportedly 16.2 months when patients in whom the majority was in stage III underwent definitive CRT [15]. Another review of 143 EC patients reported 5-year overall survival of 19.8% with median overall survival of 22.1 months when patients received definitive CRT [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Non-traversable esophageal stricture was reported to be a factor related to prognosis in EC patients receiving definitive CRT [10]. However, studies on the clinical implications of EUS non-traversability in patients with advanced locoregional squamous EC receiving preoperative CRT and esophagectomy has been limited, and we therefore sought to determine its significance in this specific group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss, related to tumor location and side effects of the treatment is frequently reported both before and during treatment (4,5). Before the start of the treatment 34-74% of patients report weight loss (6)(7)(8)(9)(10) and during treatment this is 40-57% (6,10,11). As preoperative weight loss is associated with postoperative morbidity (12)(13)(14)(15) and increased healthcare costs (4,5), it is important to recognize which patients are at risk for deterioration of nutritional status during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the present era, almost half of the patients with esophageal cancer are overweight at diagnosis (9,10,16). Literature advises an assessment of nutritional status which, next to weight, body mass index (BMI) and weight loss, also comprises parameters of muscle mass or muscle strength (17,18) as overweight may mask a compromised nutritional status.…”
Section: Introductionmentioning
confidence: 99%